Public finance - Eckstein, Otto. (Englewood Cliffs, N.J. : Prentice-Hall, 1979)
This book is an introduction to public finance, the study of the revenue and expenditure activities of government. It discusses budgets, taxes, government expenditures, and public debt
Includes index.
Includes bibliography: p. 127-128
osc 10/01/2019
Loans
Keywords: Finance, Public